2013
DOI: 10.1021/am4040976
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal Solution-Processed CuInSe2 Solar Cells with Significantly Improved Efficiency up to 9% by Morphological Improvement

Abstract: We demonstrate here that an improvement in the green density leads to a great enhancement in the photovoltaic performance of CuInSe2 (CISe) solar cells fabricated with Cu-In nanoparticle precursor films via colloidal solution deposition. Cold-isostatic pressing (CIP) increases the precursor film density by ca. 20%, which results in an appreciable improvement in the microstructural features of the sintered CISe film in terms of a lower porosity, a more uniform surface morphology, and a thinner MoSe2 layer. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 54 publications
0
22
0
Order By: Relevance
“…Further studies are accordingly in progress to enhance the densication of the absorber layer. It should be noted, however, that the present result exceeding 6% efficiency was achieved with no additional treatments of the absorber layer, such as mechanical pressing, 43 intentional Na-incorporation, 12,44 chemical etching with KCN or HCl solutions, 44,45 or annealing in a Sn-containing atmosphere. 46 Fig.…”
Section: Photovoltaic Properties Of Cztse Thin Lmsmentioning
confidence: 53%
See 1 more Smart Citation
“…Further studies are accordingly in progress to enhance the densication of the absorber layer. It should be noted, however, that the present result exceeding 6% efficiency was achieved with no additional treatments of the absorber layer, such as mechanical pressing, 43 intentional Na-incorporation, 12,44 chemical etching with KCN or HCl solutions, 44,45 or annealing in a Sn-containing atmosphere. 46 Fig.…”
Section: Photovoltaic Properties Of Cztse Thin Lmsmentioning
confidence: 53%
“…In particular, the shunt conductance (G sh ¼ 0.87 mS cm À2 ) was almost three times higher than that of the low-bandgap CuInSe 2 device with 8.33% efficiency. 43 It is thus suggested that this high G sh together with the high n resulted in the low FF. The TEM crosssectional image of the as-prepared device (Fig.…”
Section: Photovoltaic Properties Of Cztse Thin Lmsmentioning
confidence: 99%
“…However, increasing prices of rare metals, such as indium and gallium, hamper further advancement in the field of CIGS thin‐film solar cells. From this perspective, various copper‐based ternary and quaternary chalcogenide nanocrystals, such as CuInS 2 , CuInSe 2 , CuSbS 2 , Cu 3 BiS 3 , Cu 2 FeSnS 4 , Cu 2 ZnSnS 4 (CZTS), and Cu 2 ZnSnSe 4 (CZTSe), have all emerged as potential alternatives . Recently, it was shown that the band gap of Cu 2 SnS 3 and Cu 2 ZnSn(S x Se 4− x ) (CZTSSe) could be tuned by substituting tin with germanium in the crystal lattice, which resulted in enhanced device performance .…”
Section: Introductionmentioning
confidence: 99%
“…21 Furthermore, by employing a cold-isostatic pressing (CIP) technique, it was demonstrated that the microstructure of CISe lms was strongly affected by the packing density of the precursor layers. 22 However, the CIP method is not readily applicable in large-scale production processes due to the complexity of the process.…”
Section: Introductionmentioning
confidence: 99%